1991
DOI: 10.1111/j.1432-1033.1991.tb16467.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana H1 histones

Abstract: We have isolated two Arubidopsis thulium cDNA clones that encode different H1 histone proteins. The H1-3 and HI-2 proteins are 274 and 273 amino acids in length, respectively. Unlike the H1 histones within a single animal species, the two plant H1 proteins share little sequence similarity outside the protein's central globular domain. Within the globular domain, a pentapeptide that is extremely well conserved in animal Hl histones, is not found in either of the plant proteins. Southern blot analysis suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In general, apicies and young tissues contain significant amounts of mRNA, but mature tissues do not. We found that the histone H1 mRNA is a polyadenylated message (data not shown) and, in this respect, it is similar to all the other reported higher plant H1 mRNAs [9,10,21,291. In contrast, the Volvox [20] and most animal cell histone H1 mRNAs are non-polyadenylated, and those which are generally fit into the category of developmental variants or replication-independent variants.…”
Section: Speciessupporting
confidence: 88%
“…In general, apicies and young tissues contain significant amounts of mRNA, but mature tissues do not. We found that the histone H1 mRNA is a polyadenylated message (data not shown) and, in this respect, it is similar to all the other reported higher plant H1 mRNAs [9,10,21,291. In contrast, the Volvox [20] and most animal cell histone H1 mRNAs are non-polyadenylated, and those which are generally fit into the category of developmental variants or replication-independent variants.…”
Section: Speciessupporting
confidence: 88%
“…Second, and signi®cantly, the position of the ®rst intron of the A. nidulans gene is exactly conserved in several plant H1 genes. This intron is exactly in the same position as the single intron of the tomato H1 histone (Jayawardene and Riggs, 1994) and the ®rst intron of the genes encoding histones H1-1 of Arabidopsis thaliana (Gannt and Lenvik, 1991) and H1-I of Volvox carteri (Lindauer et al, 1993). This intron is not conserved in the other histone H1 genes found in the last two organisms.…”
Section: Discussionmentioning
confidence: 87%
“…No other gene encoding a linker histone is present in this organism. The A. nidulans coding sequence is shorter than animal (about 220 residues) and plant (240±274 residues) typical sequences (Gannt and Lenvik, 1991;Lindauer et al, 1993;Jayawardene and Riggs, 1994). The A. nidulans translated sequence lacks part of the amino terminus present in most histones of higher eukaryotes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In higher plants, H3 and H4 genes of wheat Tabata eta/., 1983Tabata eta/., ,1984, corn (Chaubet eta/., 1986;Gigot eta/., 1987;Phillipps eta/., 1986), rice (Wu etab, 1989b), Arabidopsis (Chaboute eta/., 1987) and alfalfa (Wu et a/., 1988) and a H I gene of Arabidopsis (Gantt and Lenvik, 1991) were isolated and their structures and sequences were analyzed. Most of the plant histone genes are dispersed in the genome except for the case of rice in which H2A, H2B and H4 genes are clustered in a 6.5 kb chromosome fragment (Thomas and PadayaW, 1983).…”
Section: Introductionmentioning
confidence: 99%